2008
DOI: 10.5702/massspec.56.181
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer Reaction Time-of-Flight Mass Spectrometry at Low Drift-Tube Field-Strengths Using an H<sub>2</sub>O-Rare Gas Discharge-Based Ion Source

Abstract: A discharge-based proton transfer reaction (PTR) ion source was operated using a mixture of H2O and rare gases such as He, Ne, Ar, and Kr in combination with a custom-built time-of-flight (TOF) mass spectrometer. In contrast to an "H2O-only" discharge, which usually functions above a field strength (E/N) of 100 Td for a drift tube, an "H2O῎rare gas"-based discharge was operated successfully at E/N values between 30 and 50 Td. (E is the electric field strength (V cm ῎1 ), N is the bu#er gas number density (mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…According to Aoki et al, NO 2 + is the predominant ion in the PTR detection of C 1 –C 2 alkyl nitrates; however, the observed fragmentation of the protonated nitrates is strongly pressure dependent and in case of CH 3 ONO 2 can give a strong protonated peak m / z 78 under certain conditions . In the present study, the peak assignment was confirmed using detection with the deuteron transfer reaction (DTR) when the H 2 O flow into the IMR was changed to D 2 O.…”
Section: Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…According to Aoki et al, NO 2 + is the predominant ion in the PTR detection of C 1 –C 2 alkyl nitrates; however, the observed fragmentation of the protonated nitrates is strongly pressure dependent and in case of CH 3 ONO 2 can give a strong protonated peak m / z 78 under certain conditions . In the present study, the peak assignment was confirmed using detection with the deuteron transfer reaction (DTR) when the H 2 O flow into the IMR was changed to D 2 O.…”
Section: Methodssupporting
confidence: 65%
“…Formaldehyde was observed at m/z 31, 49, and 67 corresponding to According to Aoki et al, 26 NO 2 + is the predominant ion in the PTR detection of C 1 −C 2 alkyl nitrates; however, the observed fragmentation of the protonated nitrates is strongly pressure dependent in case of CH 3 ONO 2 can give a strong protonated peak m/z 78 under certain conditions. 27 In the present study, the peak assignment was confirmed using detection with the deuteron transfer reaction (DTR) when the H 2 O flow into the IMR was changed to D 2 O. Figure 2b The calibrated NO 2 signal was used to estimate the trace impurity level of NO 2 as well as to measure NO 2 concentration from reaction 1a.…”
Section: Introductionmentioning
confidence: 56%
“…If the method was alleged to be superior to the previous ones, reduction of ethanol effects was obtained still with a certain loss of sensitivity, and the presence of argon in the drift‐tube could even decrease the sensitivity of certain product ions at an extent up to 5 to 10‐fold . Moreover, selective sensitivity detrimental to less polar compounds was observed, confirming previous observations made using an H 2 O‐rare gas discharge‐based ion source at low drift‐tube field strengths …”
Section: Introductionsupporting
confidence: 81%
“…11 Moreover, selective sensitivity detrimental to less polar compounds was observed, 11 confirming previous observations made using an H 2 O-rare gas discharge-based ion source at low drift-tube field strengths. 15 Non-conventional operating conditions using very large electric field strength to number density ratio E/N values in the drift-tube (where E is the electric field in the drift-tube and N is the gas number density) were also proposed recently. 7,16 With these extreme condi- 7 The main drawback of increasing the E/N value to such an extent was the large increased fragmentation of the analytes resulting in a greater proportion of non-specific low mass fragments to the detriment of protonated molecular ions or more specific ions, 16 which could be a real challenge for complex products in terms of number of volatile organic compounds (VOCs).…”
mentioning
confidence: 99%